2021
DOI: 10.3389/fendo.2021.639165
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Ameliorate Sepsis-Induced Acute Kidney Injury by Promoting Mitophagy of Renal Tubular Epithelial Cells via the SIRT1/Parkin Axis

Abstract: Sepsis is a common risk factor for acute kidney injury (AKI). Bone marrow-derived mesenchymal stem cells (BMSCs) bear multi-directional differentiation potential. This study explored the role of BMSCs in sepsis-induced AKI (SI-AKI). A rat model of SI-AKI was established through cecal ligation and perforation. The SI-AKI rats were injected with CM-DiL-labeled BMSCs, followed by evaluation of pathological injury of kidney tissues and kidney injury-related indicators and inflammatory factors. HK-2 cells were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 53 publications
1
29
0
1
Order By: Relevance
“…Guo et al ( 115 ) and Liu et al ( 116 ) found that apoptosis and pyroptosis coexist in CLP mice. Li and Liu confirmed the same results ( 117 , 118 ). Yu et al ( 108 ) found that autophagy existed in a CLP mouse model, in the early stage, autophagy was stronger, and gradually weakened over time.…”
Section: Relationship Between Various Types Programmed Cell Deathsupporting
confidence: 73%
“…Guo et al ( 115 ) and Liu et al ( 116 ) found that apoptosis and pyroptosis coexist in CLP mice. Li and Liu confirmed the same results ( 117 , 118 ). Yu et al ( 108 ) found that autophagy existed in a CLP mouse model, in the early stage, autophagy was stronger, and gradually weakened over time.…”
Section: Relationship Between Various Types Programmed Cell Deathsupporting
confidence: 73%
“…To study how miR-30b-5p participated in the regulation of autophagy, the targeted binding sites between miR-30b-5p and SIRT1 were predicted through the bioinformatics online website Transtarget 7.2 ( Figure 3A ). The regulation of SIRT1 in autophagy is repeatedly reported ( 23 , 24 , 35 ). The binding relationship between miR-30b-5p and SIRT1 was elucidated by a dual-luciferase assay ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 82%
“…MSCs play a protective role in mitochondria for renal repair mainly through the following mechanisms: 1) transfer of mitochondria to damaged proximal tubular epithelial cells ( Konari et al, 2019 ); 2) regulation of mitochondrial biogenesis by enhancing PGC1-α expression, NAD + biosynthesis, and SIRT3 activity ( Perico et al, 2017 ); 3) inhibition of mitochondria-mediated apoptosis and mitophagy (in hexavalent chromium-injured kidney) ( Yin et al, 2019 ); and 4) activation of mitophagy (in sepsis- and cisplatin-induced AKI) ( Wang et al, 2017 ; Guo et al, 2021 ). Recent studies have indicated that MSC-EVs also have a protective effect on mitochondrial damage caused by AKI, which protects TECs against injury by reducing mitochondrial fragmentation, normalizing mitochondrial membrane potential, and reversing mitochondrial DNA deletion and oxidative phosphorylation defects ( Cao et al, 2020 ; Zhao et al, 2021 ).…”
Section: Fatty Acid β-Oxidation and Stem Cell-based Therapymentioning
confidence: 99%